ANALISIS PENGARUH PENGUMUMAN RIGHT ISSUE TERHADAP ABNORMAL RETURN DAN VOLUME PERDAGANGAN SAHAM DI BURSA EFEK INDONESIA PERIODE TAHUN 2009 – KUARTAL 3 TAHUN 2012 - Maria Gladys Jessica Kamalsah; Yunia Panjaitan (Universitas Katolik Indonesia Atma Jaya, 2015)
The availability of the information on capital market transactions will affect decisions of investors who will also determine the price of the stock market. This study was conducted to examine the effect of the announcement of the rights issue on stock prices and trading volume. Sample for this study was 63 companies who do right issue on the Stock Exchange during 2009 - 3rd quarter of 2012. The data collected consisted of daily return actual data, the IHSG daily data as market returns, and daily stock trading volume from each sample company. The result of the analysis showed that there were no significant differences in average abnormal return, but there are significant differences in the average stock trading volume. So, it can be concluded that the announcement of the rights issue contains information for investors, but did not contain information to make an investment decision.